2023
DOI: 10.3390/biology12060861
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Reactive Bone Stromal Fibroblasts in 3D Models of Prostate Cancer Bone Metastases

Abstract: A dynamic interplay between prostate cancer (PCa) cells and reactive bone stroma modulates the growth of metastases within the bone microenvironment. Of the stromal cells, metastasis-associated fibroblasts (MAFs) are known to contribute but are the least studied cell type in PCa tumour progression. It is the aim of the current study to establish a biologically relevant 3D in vitro model that mimics the cellular and molecular profiles of MAFs found in vivo. Using 3D in vitro cell culture models, the bone-derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…The interaction between metastatic cancer cells and the bone microenvironment plays a crucial role in driving cellular and molecular changes in tumor cells to promote their migration within the bone [6,7]. Efforts have been put into investigating interactions of metastatic cancer cells with the bone microenvironment [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The interaction between metastatic cancer cells and the bone microenvironment plays a crucial role in driving cellular and molecular changes in tumor cells to promote their migration within the bone [6,7]. Efforts have been put into investigating interactions of metastatic cancer cells with the bone microenvironment [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that smaller, poorly crystalline HA particles enhanced cancer cell adhesion and growth relative to larger, more crystalline HA particles, confirming HA particles' role in bone metastasis. Sieh et al [6] studied the interactions of osteoblast cells and CaP cells with polycaprolactonetricalcium phosphate (mPCL-TCP) scaffolds by wrapping mPCL-TCP scaffold within the osteoblast sheets to create a 3D matrix for CaP cell culture. CaP cells were then seeded on this 3D matrix to study CaP metastasis in a bone-like microenvironment, showing that CaP cell-bone matrix interactions lead to elevated levels of matrix metalloproteinase (MMPs) and prostate-specific antigens (PSAs), which are all associated with CaP metastasis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation